Acute effects of ambient nitrogen dioxide exposure on serum biomarkers of nervous system damage in healthy older adults - Jie Song; Rongrong Qu; Beibei Sun; Yinbiao Wang; Renjie Chen; Haidong Kan; Zhen An; Hui Wu; Juan Li; Jing Jiang; Yange Zhang; Weidong Wu (Ecotoxicology and Environmental Safety, 2023)
Ambient nitrogen dioxide (NO2)-induced adverse health effects have been studied, but documented evidence on neural systems is limited. This study aimed to determine the acute effect of NO2 exposure on nervous system damage biomarker levels in healthy older adults. Five rounds of follow-up among 34 healthy retired people were scheduled from December 2018 to April 2019 in Xinxiang, China. The real-time NO2 concentrations were measured using a fixed site monitor. Serum samples were acquired during each round to measure nervous system damage biomarker levels: brain-derived neurotrophic factor (BDNF), neurofilament light chain (NfL), neuron-specific enolase (NSE), protein gene product 9.5 (PGP9.5), and S100 calcium-binding protein B (S100B). A linear mixed-effect model was incorporated to analyze the association between short-term NO2 exposure and serum concentrations of the above-mentioned biomarkers. Stratification analysis based on sex, educational attainment, glutathione S-transferase theta 1 gene (GSTT1) polymorphism, and physical activity intensity was conducted to explore their potential modification effect. The NO2 concentration ranged from 34.7 to 59.0 µg/m3 during the study period. Acute exposure to ambient NO2 was significantly associated with elevated serum levels of NfL, PGP9.5, and BDNF. In response to a 10 µg/m3 increase in NO2 concentration, NfL and PGP9.5 levels increased by 76 % (95 % confidence interval [CI]: 12–140 %) and 54 % (95 % CI: 1–107 %) on the lag0 day, respectively, while BDNF levels increased by 49 % (95 % CI: 2–96 %) at lag4 day. The estimated effect of NO2 on NSE levels in GSTT1-sufficient participants was significantly higher than that in GSTT1-null participants. Intriguingly, the estimation of NO2 on PGP9.5 levels in females was significantly higher than that in males. Most two-pollutant models showed robust results, except for O3, which might have had confounding effects on NO2-induced BDNF stimulation. In summary, acute exposure to NO2 was associated with increased levels of serum nervous system damage biomarker levels including NFL, PGP9.5, and BDNF. The present study provided insights into NO2 exposure-induced adverse neural effects.